Legal Protection for Remote Working Workers: Comparison of Positive Law Between Indonesia and United States - Gultom, Jeges Imanuelita; Mayca, Ofelica Ruth; Simarmata, Prayusti Sarah; Sihombing, Sherina Elizabeth; Anggusti, Martono (Manunggal Halim Jaya, 2025)
The development of increasingly diverse and time-spanning work arrangements: remote work systems need to be known and understood with certainty and legal protections for remote employees. Remote Working workers are prone to non-compliance with the following rights in the company's work cycle. The United States, one of the developed countries, has regulations to protect remote workers, and interpreting these regulations according to the situation in Indonesia can be helpful if they are implemented appropriately. This study aims to obtain reference materials regarding regulations that can be applied in Indonesia to ensure legal protection for remote workers. This research is comparative legal research using literature studies. In Indonesia, Remote Working worker regulations do not exist specifically, so they are still based on the Job Creation and Manpower Law. Meanwhile, in the United States, regulations for Remote Working workers have existed since 1990 until now. Despite the differences in legal systems between Indonesia and the United States, efforts are being made to coordinate appropriate regulations to develop government regulations in line with the increasing diversity of employment systems. Therefore, the government must clarify and follow up on determining legal protection for remote workers.